The relationship between sociologic aspects and rheumatic mitral valve disease severity in an endemic region - Alici, H.; Davutoglu, V.; Yuce, M.; Cakici, M.; Davutoglu, S.; Ercan, S. (Oxford Univ Press, 2017)
[Abstract Not Available]